This is How We are at Home: Typology and Shifting Parenting Authority in Early Childhood - Sapendi, Sapendi; Suratman, Bayu (Al-Athfal: Jurnal Pendidikan Anak, 2024)
Purpose – Parenting Islamism not only makes religion a teaching material in children’s education, but more than that, religion is used as an ideology that displays Islamic symbols in parenting actions in the public sphere. The emergence of Islamism parenting practices is a response to traditional parenting practices and modern parenting practices.  This study aims to explore the practice of parenting in millennial families based on the ideology of Islamism in Pontianak City. Design/methods/approach – This research method uses the Mixed Methods Research approach, which is a combination of qualitative and quantitative methods. The qualitative method in this study provides an understanding of the shifting in parenting authority carried out by millennial parents with the ideology of Islamism. Meanwhile, the quantitative is carried out to measure the variables of parenting typology objectively. Data analysis in this study was carried out; first, the data was reduced; second, data categorization; third, data preparation; fourth, data verification; fifth, the configuration of the relationship between the inference of the problem formulation; sixth, the data is analyzed with theory. Findings – The findings of this study show that millennial parents of Islamism groups use mixed parenting, which is a combination of several parenting models according to the condition of the child, be it authoritarian, authoritative, and permissive. The findings of this study also show that there is a shift in parenting authority in Islamism millennial families, which is influenced by new media so that parents idolize popular ustadz from Islamism groups. Research implications/limitations – The shift in authority in parenting has implications for parental figures or references in parenting due to the presence of new authorities on social media, namely public figures or micro-celebrities. This research is not final, and there are still many limitations in relevant cases, informants, and theories, so further research is needed to accommodate other new findings in parenting studies in millennial families of Islamism groups with a larger number of informants in Indonesia. Practical implications – This study shows that parenting practices carried out by parents are inseparable from religious ideology, which has an impact on parenting in early childhood. This study emphasizes that parenting practices in Muslim parents are not uniform, even in religiously homogeneous families. Originality/value – This study provides a new perspective in parenting studies because it examines from the perspective of parents’ religious ideology. Paper type Research paper